2022
DOI: 10.3389/fpsyg.2022.909737
|View full text |Cite
|
Sign up to set email alerts
|

Are Adverse Childhood Experiences Associated With Being in the System of Care?

Abstract: BackgroundAdverse childhood experiences (ACEs) can cause serious mental problems in adolescents and therefore may expected to be associated with higher use of psychosocial care, potentially varying by type of specific ACE. The aim of our study is to explore the association of the number of ACE and types of specific ACE with entering and using psychosocial care.MethodsWe used data from the Slovak Care4Youth cohort study, comprising 509 adolescents from 10 to 16 years old (mean age 13.2 years, 48.6% boys). We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Globally, a systematic review revealed that two‐thirds of youth younger than 18‐years‐old have experienced ACEs (Carlson et al, 2019). A few studies have examined ACEs outcomes among early, middle, and late adolescents in different cultural contexts, such as the United States (Barnhart et al, 2022; Bomysoad & Francis, 2020; Weller et al, 2021), Slovakia (Lackova Rebicova et al, 2022), Hungary (Kovács‐Tóth et al, 2021), and Thailand (Myat Zaw et al, 2022). ACEs can induce mental (Barnhart et al, 2022; Weller et al, 2021) and physical health issues (Kovács‐Tóth et al, 2021), as well as substance abuse (Bomysoad & Francis, 2020) and poor academic success (Myat Zaw et al, 2022) during the adolescence period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, a systematic review revealed that two‐thirds of youth younger than 18‐years‐old have experienced ACEs (Carlson et al, 2019). A few studies have examined ACEs outcomes among early, middle, and late adolescents in different cultural contexts, such as the United States (Barnhart et al, 2022; Bomysoad & Francis, 2020; Weller et al, 2021), Slovakia (Lackova Rebicova et al, 2022), Hungary (Kovács‐Tóth et al, 2021), and Thailand (Myat Zaw et al, 2022). ACEs can induce mental (Barnhart et al, 2022; Weller et al, 2021) and physical health issues (Kovács‐Tóth et al, 2021), as well as substance abuse (Bomysoad & Francis, 2020) and poor academic success (Myat Zaw et al, 2022) during the adolescence period.…”
Section: Introductionmentioning
confidence: 99%
“…ACEs can induce mental (Barnhart et al, 2022; Weller et al, 2021) and physical health issues (Kovács‐Tóth et al, 2021), as well as substance abuse (Bomysoad & Francis, 2020) and poor academic success (Myat Zaw et al, 2022) during the adolescence period. Consequently, ACEs lead to higher healthcare visits among adolescents (Bhattarai et al, 2021; Lackova Rebicova et al, 2022). The evidence reveals that although ACEs may negatively influence adolescents' well‐being (Kelifa et al, 2021), this warrants examination in various cultural contexts because subjective well‐being regards individuals' interests and positive effects (Diener, Heintzelman, et al, 2017) as distinctively shaped by culture (Tov & Diener, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a survey carried out in China proved that resilience plays an important role as a mediator between ACEs and suicidal behaviors in youths [26]. Another study in Slovakia [27] underlined the role of resilience as a mediator between ACEs and emotional and behavioral problems. Unfortunately, few researches have explored the role of resilience in this pathway worldwide.…”
Section: Introductionmentioning
confidence: 99%